China University Teachers' Expectation and Motivation for Overseas Training Under the Background of "the Belt and Road Initiative" - Junhao, Chen (UNIVERSITI MALAYSIA SARAWAK, 2024)
The Belt and Road Initiative has presented both opportunities and challenges for China and countries along its route. The primary issue facing Chinese university teachers lies in their limited enthusiasm for engaging in internationalization efforts, despite policy drives aimed at fostering global development via the Belt and Road Initiative. The key challenge is to identify the expectations and underlying factors influencing teachers' decisions to participate in overseas programs, and to assess the effectiveness of cross-cultural training in motivating their involvement. An innovative simplification of the expectancy-value theory model is achieved by intertwining it with self-determination theory for exploring, through mixed methods, the expectations and motivations of teachers' participation in overseas projects. 505 teachers from six universities in central China participated in the questionnaire survey (489 valid, with a response rate of 97%), which confirmed diverse expectations regarding international training and examined several influential factors. The quantitative findings back up H1-H6 and show H7-H8 have a mediating role, but H9-H10 are not supported. It underscores the significance of cultural milieu, socializers’ behaviors, cognition, and motivational beliefs, with cognition functioning as a mediator. Qualitative interviews were conducted with 27 university teachers who have received or are undergoing overseas training to reinforce the impact of cross-cultural training on their professional growth. Competence, autonomy, relatedness, and satisfaction shape motivation within a supportive environment that meets expectancy and basic psychological needs, in line with expectancy-value theory and self-determination theory principles. Methodologically, it employs mixed methods, introducing new measurement scales. Contextually, it contributes to BRI collaboration. Practically, it guides policymakers in formulating educational indicators, aids in talent programme development, informs teaching strategies for educators, and serves as a reference for future research and talent training at universities, enhancing international cooperation and talent development. Keywords: BRI, Cross-Culture Training, Expectancy Value, University Teachers